Media coverage and macroeconomic information processing - Alexandra Niessen-Ruenzi (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
This paper investigates how media coverage in°uences macroeconomic information processing at the bond market. I provide evidence that a high media coverage of an economic topic increases investor attention prior to the release of the corresponding economic indicator: High media coverage of the business cycle leads to a stronger market reaction to the release of gross domestic product, industrial production and IFO business index than low media coverage. High media coverage of the price level increases the market reaction to the release of producer and consumer price index than low media coverage. High media coverage of unemployment leads to a stronger market reaction to the release of the unemployment rate than low media coverage.
Keywords: G23; E44; G14; 330; Media Coverage; Information Processing; Economic Indicators; Rentenmarkt; Informationsverbreitung; Wirtschaftsinformation; Kommunikationsmedien; Konjunkturindikator; Deutschland